2002
DOI: 10.1785/0120000914
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Aftershock Sequence of the 1999 Mw 7.1 Hector Mine Earthquake: Implications for Aftershock Hazard

Abstract: We investigate the spatial and temporal seismicity parameters and the related probabilistic aftershock hazard for the aftershock sequence of the 1999 M w 7.1 Hector Mine mainshock and compare it with the neighboring 1992 M w 7.3 Landers sequence. Using a catalog of 11,000 earthquakes, we determine the earthquake size distribution (b-value), the aftershock decay rate (p-value), and the seismic activity rate (a-value). The b-values are high (b Ͼ 1.2) within the rupture area, significantly lower (b Ϸ 0.7) north o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 65 publications
4
49
0
Order By: Relevance
“…Low variance (0.17, Table 3) indicates a good fit of homogeneous stress tensor to the observed focal mechanism, and shows low heterogeneity of the stress field (Michael et al, 1990;Lu et al, 1997;Wiemer et al, 2002;Bohnhoff et al, 2006;Görgün et al, 2010). The results from the stress tensor inversions based on 23 focal mechanisms are shown in map view in Fig.…”
Section: Analysis Of Stress Tensorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Low variance (0.17, Table 3) indicates a good fit of homogeneous stress tensor to the observed focal mechanism, and shows low heterogeneity of the stress field (Michael et al, 1990;Lu et al, 1997;Wiemer et al, 2002;Bohnhoff et al, 2006;Görgün et al, 2010). The results from the stress tensor inversions based on 23 focal mechanisms are shown in map view in Fig.…”
Section: Analysis Of Stress Tensorsmentioning
confidence: 95%
“…10 (blue bars). Wiemer et al (2002) concluded that a low degree of heterogeneity in stress field (variance 0.2) indicates uniformity. There is no significant variance in stress tensor orientations (variance 0.2).…”
Section: Analysis Of Stress Tensorsmentioning
confidence: 99%
“…They are used when examining earthquake statistics, as in b-value studies (e.g., Wiemer et al, 2002;Wyss et al, 2004;Ghosh et al, 2008), when interpreting earthquake rates, as in studies of repeating earthquakes (e.g., Nadeau and Johnson, 1998;Templeton et al, 2008;Werner and Sornette, 2008;Taira et al, 2014), and when comparing geodetic and seismic observations, as in studies of postseismic slip (e.g., Bell et al, 2012;Fattahi et al, 2015;Hawthorne et al, 2016). Here, we use an empirical Green's function approach to estimate the relative moments of about 1600 earthquakes near San Juan Bautista, California.…”
Section: Introduction: Background On Magnitude Estimatesmentioning
confidence: 99%
“…Large aftershocks can be particularly hazardous if they occur in populated areas such as the M w 5.80 aftershock to the 1999 M w 7.40 Izmit, Turkey, earthquake. This aftershock killed 7 and injured a further 420 people (Wiemer et al 2002). Toda et al (1998), and Wiemer and Katsumata (1999) systematically analyzed the spatial distribution of seismicity within aftershock zones.…”
Section: Introductionmentioning
confidence: 99%